Individual needs - Jaywant, Sheela (Research and Humanities in Medical Education, 2020)
<span style="display: inline !important; float: none; background-color: #ffffff; color: rgba(0, 0, 0, 0.84); font-family: 'Noto Sans',-apple-system,BlinkMacSystemFont,'Segoe UI','Roboto','Oxygen-Sans','Ubuntu','Cantarell','Helvetica Neue',sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">This poem is about Plastic Surgery, using two sample patients, one who has a very large bosom, making daily living impossible, and the other who has virtually no breast tissue, making her husband unhappy. It's also about how plastic surgery plays a role in the functioning/well-being of a patient. It's more than about looking pretty.